LAND SURFACE CHANGES DUE TO BUKITTINGGI CITY EARTHQUAKE USING THE 2019-2020 DInSAR METHOD - Saiyidinal Fikri; Desi Syafriani; Fitra Hasanah (Universitas Teknokrat Indonesia, 2022)
Bukittinggi city is in the sink segmentation